Exploration of Endophyte Bacteria as Bio-Agent of Fusarium sp. on Jack Bean (Canavalia ensiformis) Under In-Vitro Testing - Rahmadani, Pradina; Aini, Luqman Qurata (Journal of Tropical Plant Protection, 2024)
Indonesia is the tropical country that becomes the home of millions type of flora such as jack bean (Canavalia ensiformis). This plant has not gotten enough attention from locals as a beneficial commodity. The purpose of this research is to find out the potential of endophyte bacteria of jack bean as bio-agent to control the pathogenic attack on the jack bean caused by Fusarium sp. The step of research including sample collecting, isolation and identification of pathogenic fungus, isolation, and purification of endophyte bacteria from the root of jack bean plant, selection of endophyte bacteria as the antagonist of pathogenic fungus, inhibition test of endophyte bacteria against the fungus under in-vitro testing, and lastly, identification of bacteria. The result of the test used completely randomized design with 6 treatments and 4 replications. The result of research is there are 10 bacterial isolates. From the selection process, there are four isolates that are proven to inhibit Fusarium sp. as the fungal target, shown by the high percentage of fungal growth inhibition from antagonist test. At the end of the antagonist test, it was resulting in CE8 treatment as the highest percentage of fungal growth inhibition, reaching 76% in result. Characterization and identification were carried out to the 4 isolates, resulting in discovery of CE1 and CE5 coded bacterial isolates belong to Erwinia sp., and CE7 and CE8 belong to Clostridium sp.